The harlequin years music in Paris 1917-1929 - Nichols, Roger 1939- (Thames & Hudson, 2002)
Based on the author's series of 12 programmes broadcast on BBC Radio 3, this is an account of the classical music scene in Paris between 1917 and 1929. It notes the currents of these "turbulent waters", as well as the numerous personalities, and a few statistics.
Keywords: Geschichte 1917-1929; Musikliv - Frankrike - Paris - 1900-talet; Musik; Paris